Investigating the value-based strategic leadership on private higher education performance: Evidence from West Java and Banten, Indonesia - Rasyid, Mohammad Kurniadi; Disman, Disman; Senin, Samsul Hadi; Purwaningsih, Dyah (Universitas Jambi, Indonesia, 2026)
This study investigates whether value-based strategic leadership improves organizational performance in private higher education institutions. An explanatory survey was conducted across West Java and Banten, Indonesia. Data from 212 valid respondents (lecturers, administrative staff, and administrative staff from 120 higher education institutions) were analyzed using partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4. The findings confirm a strong positive effect of strategic leadership on organizational performance (β = 0.824; t = 29.257; p < .001) with substantial explanatory power (R² = 0.679). Measurement model assessment indicates strong internal consistency (Cronbach’s α = 0.923–0.966), convergent validity (AVE = 0.592–0.764), and acceptable discriminant validity (HTMT = 0.863). Descriptive results indicate that leadership is perceived as effective (mean = 3.52/5), while performance is perceived as high overall (mean = 3.48/5), although staff satisfaction and financial capability remain the weakest performance facets.